Kyphoplasty and intra-operative radiotheray, combination of kyphoplasty and intra-operative radiation for spinal metastases: technical feasibility of a novel approach - Schmidt, René Steffen; Wenz, Frederik; Reis, Tina; Janik, Karolin; Bludau, Frederic; Obertacke, Udo (International orthopaedics, 2012)
Purpose: To evaluate whether this new method is clinically applicable after theoretical and cadaver testing. Methods: The incidence of spinal metastases requiring therapy is increasing, due to enhanced life expectancy. Due to results from studies with epidural compression a combined surgical and radiation therapy is often chosen. Minimal invasive cement augmentation is an increasingly used technique, due to fast pain relief and immediate stabilisation. On the other hand, stereotactic radiosurgery is considered to provide a more durable response and better local disease control than conventional radiotherapy with the application of higher doses. Therefore the combination of cement stabilisation and simultaneous intra-operative radiation with immediate stabilisation and high-dose radiation could be an interesting therapeutic option. The results of a clinical feasibility study are presented. Results:17 patients could be treated with the new method. In two patients (10%) intra-operative radiation could not be applied. No surgical interventions for complications were required. Conclusions: Summarizing Kypho-IORT is technically feasible with an intra-operative risk profile comparable to sole kyphoplasty and a shorter treatment time and hospitalisation for the patients compared to conventional multifraction radiation. Radiation could not be applied in 10% of cases due to technical difficulties. The results of this feasibility study permit further evaluation of this new technique by a dose escalation study which is currently in preparation.